Analisis Permintaan Smartphone Samsung Galaxy Android (Studi Kasus Mahasiswa Fakultas Ekonomi Universitas Riau) - Dio Prahmana; Zulkarnaini '; Hendro Ekwarso (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research had done to known the purpose of factors that influenced Samsung Galaxy Android Smartphone demand in Economic Faculty of Riau University. In this research used primary and secondary data by using analysis method descriptive quantitative analysis. The population in this research is all of students in Economic Faculty of Riau University, and total sample is 98 students from the population by using Slovin formula. From this research that known the factors that influenced Samsung Galaxy Android Smartphone demand in Economic Faculty of Riau University is price, atribute or spesification and brand image.Keywords: demand, Samsung Galaxy Android Smartphone, price, atribute or spesification, and brand image.